The Effect of Motivation to Transfer Mediation on the Relationship of Individual Characteristics and Work Environment on the Transfer of Learning of Nurses in Hospitals - Arum Ratna Pratiwi; Oscar Jayanagara (Green Publisher Indonesia, 2025)
This study aims to determine the direct effects of training design, individual characteristics, work environment, and motivation to transfer on transfer of learning, as well as the indirect effects through the mediation of motivation to transfer. This research is a quantitative study with a cross-sectional design. Respondent data collection using a purposive sampling technique, with questionnaires as a data collection tool, was filled out by 346 nurses in six Siloam Hospitals and then analyzed with PLS-SEM 4. The findings in this study are motivation to transfer, training design, individual characteristics, and work environment have a significant positive effect on the transfer of learning. Training design, individual characteristics, and work environment have an indirect significant positive effect on the transfer of learning through motivation to transfer. It was also found that training design has an indirect significant positive effect on motivation to transfer through individual characteristics. From the mediation analysis test, it is known that motivation to transfer mediated the relation between individual characteristics and work environment to transfer of learning. Furthermore, individual characteristics mediated the relationship between training design and motivation to transfer.